(untitled) (International Journal Online of Humanities, 2017)
Dr Radhakrishnan’s thinking was Upanishadic. He also firmly believed in the birth of a new order based on ancient Indian wisdom. Drawing his inspiration from the Vedas, the Upanisads and the Gita, Radhakrishnan believed that humanity must become one. What kind of religion did Radhakrishnan advocate? Not a credal or dogmatic one, not an intellectual theology disputing over dogmas and contemplations. Radhakrishnan takes pride in the fact that Hinduism is not bound up with a creed or a dogma, with a founder – prophet or a historical personality, with a book like the Bible or the Quran, but a “persistent search for truth on the basis of a continuously renewed experience”. Radhakrishnan, as an ardent Hindu, could not transcend Hinduism itself. He was respectful of all religions, but it is ultimately Hindu standards by which he judged other religions. Hinduism was always for him the ideal religion, of course, a Hinduism re-interpreted, purged of all that he found distasteful in it. That President Radhakrishnan was a dhvajasthambalam in the temple of our nation’s consciousness: upright and resplendent in rough weather and fair, inspiring us to a higher purpose. K R Srinivas Iyengar noted that without the reserves of the spirit, the inner poise, the hidden fire, all other endowments cannot count for much. And the spirit that moved and sustained our ancient Indian Rishis and Acharyas is not foreign to Professor Radhakrishnan